1990
DOI: 10.1111/j.1464-5491.1990.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids and Lipoproteins in Type 2 Diabetic Patients with Persistent Microalbuminuria

Abstract: To investigate whether persistent microalbuminuria is related to altered levels of both lipids and apolipoproteins in Type 2 diabetes mellitus serum total-cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol, apolipoprotein A-I, and apolipoprotein B were measured by standard methods in a group of Type 2 diabetic patients affected by persistent microalbuminuria (albumin excretion rate (AER) 20-200 micrograms min-1) as compared with a group of sex- and age-matched non-microalbuminuric patients (AER less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…Other study groups have reported that raised triglyceride values were measured in the presence of microalbuminuria, whereas the findings with regard to total cholesterol varied [22,23]. In the present study it could be shown that the triglyceride level has an independent effect on the progression of nephropathy.…”
Section: Discussioncontrasting
confidence: 51%
“…Other study groups have reported that raised triglyceride values were measured in the presence of microalbuminuria, whereas the findings with regard to total cholesterol varied [22,23]. In the present study it could be shown that the triglyceride level has an independent effect on the progression of nephropathy.…”
Section: Discussioncontrasting
confidence: 51%
“…This relationship has not been consistently found in NIDDM patients (30,48,49). In this study, an inverse relationship, of borderline significance (P = 0.08), between microalbuminuria and HDL cholesterol was established.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, the predictive power of microalbuminuria was not demonstrated to be independent of either hypercholesterolemia or smoking, which are known to be important CVD risk factors in diabetes (21). Several studies have reported cross-sectional associations between plasma lipids and lipoproteins and albuminuria in IDDM (11,22) and NIDDM (12,23,24) and also between smoking and albuminuria in IDDM (10) and NIDDM (25). These factors could confound an apparent link between microalbuminuria and morbidity and mortality outcomes.…”
Section: Discussionmentioning
confidence: 99%